The Optimization of Tuna Fish and Banana Blossoms into Abon Modified Products in Puger District, Jember Regency - Ninna Rohmawati; Anita Dewi Moelyaningrum; Eri Witcahyo (LP2M Universitas Jember, 2019)
Puger is the largest fish producing sub-district in Jember district, which also has a prevalence of high nutritional problems. During this time there are “mitra” who are a group of fish processors and marketers (POKLAHSAR) namely